2006
DOI: 10.1002/qua.20989
|View full text |Cite
|
Sign up to set email alerts
|

Computational and spectroscopic studies concerning the solvatochromic behavior of 1,3‐disubstituted azulenes

Abstract: ABSTRACT:Estimates of excited-state dipole moments for various 1,3-disubstituted azulenes possessing electron-withdrawing substituents, using the CIS/6-31ϩG(d,p) model, reveal that unlike azulene, the excited-state dipole moments are generally in the same direction as, although smaller in magnitude than, their ground-state counterparts. This gives rise to hypsochromic shifts in the UV-visible spectrum of these dipolar indicator molecules as solvent polarity is increased. Furthermore, B3LYP density functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Although much research has already been performed to explore the anomalous emission in azulene derivatives, these molecules are still used as a building block to promote anti-Kasha emission. , On top of that, because of its significant permanent dipole moment and its ease for yielding chemical substitutions, tailored-made azulene derivatives are promising candidates for their use in organic field effect transistors and solar cells. , Extensive and exhaustive experimental data on the photophysical properties of azulene derivatives are available in the literature , so that these molecules offer the perfect platform to test the validity of our approximations and will permit us to understand and rationalize the observed trends in the excited-state lifetimes and quantum yields of the series of azulene derivatives. More in detail, the following substituted azulene derivatives are investigated in this work: azulene ( 1a ), guaiazulene or 1,4-dimethyl-7-isopropylazulene ( 1b ), 1,3-dichloro- ( 1c ), 1,3-dibromo- ( 1d ), and 5,6-dichloroazulene ( 1e ) (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Although much research has already been performed to explore the anomalous emission in azulene derivatives, these molecules are still used as a building block to promote anti-Kasha emission. , On top of that, because of its significant permanent dipole moment and its ease for yielding chemical substitutions, tailored-made azulene derivatives are promising candidates for their use in organic field effect transistors and solar cells. , Extensive and exhaustive experimental data on the photophysical properties of azulene derivatives are available in the literature , so that these molecules offer the perfect platform to test the validity of our approximations and will permit us to understand and rationalize the observed trends in the excited-state lifetimes and quantum yields of the series of azulene derivatives. More in detail, the following substituted azulene derivatives are investigated in this work: azulene ( 1a ), guaiazulene or 1,4-dimethyl-7-isopropylazulene ( 1b ), 1,3-dichloro- ( 1c ), 1,3-dibromo- ( 1d ), and 5,6-dichloroazulene ( 1e ) (see Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Although much research has already been performed to explore the anomalous emission in azulene derivatives, these molecules are still used as a building block to promote anti-Kasha emission. 16,[28][29][30] On top of that, due to its permanent dipole and its ease for yielding chemical substitutions, tailored-made azulene derivatives are promising candidates for their use in organic field effect transistors and solar cells. 31,32 Extensive and exhaustive experimental data on the photophysical properties of azulene derivatives are available in the literature, 33,34 so that these molecules offer the perfect platform to test the validity of our approximations and will permit us to understand and rationalize the observed trends in the excited state lifetimes and quantum yields of the series of azulene derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…According to Kasha’s rule, organic luminogens normally emit from the lowest excited state irrespective of the excitation energy. In contrast, some cases (e.g., azulenes, thiones, pyrene) have been found that can produce anomalous emission from higher excited states due to their ultrafast radiative rate or large S 2 –S 1 energy gap. These so-called anti-Kasha’s rule emissions can ideally improve the fluorescent quantum efficiency by avoiding additional consumption from internal conversions and other forms of electronic relaxation processes, and are hence of great theoretical and experimental interest. Although a number of prototypes that can exhibit anti-Kasha’s rule emissions have been disclosed, thus far the emissive transfer among different high-excited states has been poorly addressed, simply because these excited states basically bear quite small energy gaps in between. As a result, it has become urgent to develop a chemical strategy that can tune distinct emission from different high-excited states especially from the perspective of building practical and distinguishable sensing materials.…”
Section: Introductionmentioning
confidence: 99%